2023
DOI: 10.1186/s13046-023-02634-z
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal cargos-mediated metabolic reprogramming in tumor microenvironment

Abstract: Metabolic reprogramming is one of the hallmarks of cancer. As nutrients are scarce in the tumor microenvironment (TME), tumor cells adopt multiple metabolic adaptations to meet their growth requirements. Metabolic reprogramming is not only present in tumor cells, but exosomal cargos mediates intercellular communication between tumor cells and non-tumor cells in the TME, inducing metabolic remodeling to create an outpost of microvascular enrichment and immune escape. Here, we highlight the composition and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 296 publications
0
25
0
Order By: Relevance
“…Furthermore, RAS family, has a mutation rate of 15% in OC, and these mutations can lead to metabolic reprogramming, which is one of the most important hallmarks of cancer cells [ 44 ]. Metabolic reprogramming occurs through multiple metabolic changes such as in glucose, fatty acid and glutamine, which can affect the interactions between cancer cells and TME, leading to malignant biological process including cell migration, angiogenesis and immune escape [ 45 ]. As findings in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RAS family, has a mutation rate of 15% in OC, and these mutations can lead to metabolic reprogramming, which is one of the most important hallmarks of cancer cells [ 44 ]. Metabolic reprogramming occurs through multiple metabolic changes such as in glucose, fatty acid and glutamine, which can affect the interactions between cancer cells and TME, leading to malignant biological process including cell migration, angiogenesis and immune escape [ 45 ]. As findings in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cancerous tissue, cancer cells showed the highest uptake of glutamine as compared with other cell subsets in the TME, as evidenced by positron emission tomography (PET) tracers [ 170 ]. In the context of tumorigenesis, the uptake of glutamine by cancer cells can be promoted by exosomes derived from various types of cellular components in the TME through different mechanisms [ 171 ]. Zhang et al discovered that M2 macrophage-derived exosomal miR-193b-3p enhanced the proliferation, migration, invasion, and glutamine uptake of PCs by targeting tripartite motif (TRIM)-containing protein TRIM62, resulting in the decrease of c-Myc ubiquitination [ 172 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…On the contrary to the role of metabolic reprogramming in fostering the growth of cancer cells, metabolic deregulation and imbalance in immune cells within the TME have been reported to drive immune evasion and to limit therapeutic outcomes [ 248 ]. Given the manifold roles of exosomal cargoes in mediating metabolic reprogramming in TIME [ 171 ], it is worth noting that simultaneous targeting of dysregulated metabolic reprogramming may help to improve the response to cancer immunotherapy and deserves further exploration. Actually, a recent study by Hernández-López et al has already demonstrated that dual targeting of cancer metabolome and stress antigens (such as NKG2D ligands or CD277) could affect transcriptomic heterogeneity of engineered T cells and improve their efficacy [ 249 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“… 10 Recent findings indicate that TDSEVs harbor a diverse array of molecular constituents, including lipids, membrane-associated proteins, long noncoding RNAs (lncRNAs), and miRNAs, 10 which contribute to key processes in tumor initiation and progression, such as angiogenesis, proliferation, metastasis, and immune evasion. 11 Moreover, the prominent biological features of TME, such as hypoxia, extracellular acidosis and low nutrients, can induce heterogeneous changes in TDSEVs release, cargo composition and transport, which are also key determinants for malignancy, proliferation, and metastasis. 9 , 12 , 13 Therefore, it is imperative not to overlook the role of TDSEVs in maintaining the survival environment of tumor cells and promoting their invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%